2008
DOI: 10.4103/0378-6323.39727
|View full text |Cite
|
Sign up to set email alerts
|

Oral isotretinoin is as effective as a combination of oral isotretinoin and topical anti-acne agents in nodulocystic acne

Abstract: Isotretinoin produces gratifying results in patients of nodulocystic acne in Indian conditions. Addition of topical antiacne agents does not alter the final outcome. This addition is well tolerated but requires careful monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…[6263] It is the only drug that affects all four pathogenic factors implicated in the etiology of acne.…”
Section: Systemic Therapymentioning
confidence: 99%
“…[6263] It is the only drug that affects all four pathogenic factors implicated in the etiology of acne.…”
Section: Systemic Therapymentioning
confidence: 99%
“…[1] This disease is a multifaceted disorder of the sebaceous glands. [2] Over the last 3 decades, scientific understanding of the pathogenesis of acne has increased considerably. Acne vulgaris is traditionally managed with a variety of topical and systemic medications.…”
Section: Introductionmentioning
confidence: 99%
“…found no significant benefit in the combination of topical anti-acne and isotretinoin over isotretinoin alone in improving nodulocystic acne vulgaris. [4] However, in our study, the significant efficacy observed in the use of topical 5% dapsone in a similar setting in reducing the count of lesions in weeks 4, 8 and 12, is probably due to the additional anti-inflammatory effect of dapsone. In a study by Tanghetti et al .…”
Section: Discussionmentioning
confidence: 50%
“…Antibiotics play a pivotal role in treatment. [4] Dapsone (4, 4′-diaminodiphenylsulfone) is a drug of the sulfone class and was discovered in 1908. [5] Oral dapsone has demonstrated efficacy in acne, but was associated with severe side-effects such as anemia, which was particularly serious in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency.…”
Section: Introductionmentioning
confidence: 99%